Aesthetics of sorrow : the wailing culture of yemenite-jewish women - Gamliʼel, Ṭovah, 1965- (Wayne State University Press, 2014)
Decodes the cultural and psychological meanings of the "wailing culture" following the death of a member of the Yemenite Jewish community, based on anthropological research among Yemenite Jewish communities in Israel in 2001-2003
Keywords: Jews, Yemeni -- Funeral customs and rites -- Israel.; Weepers (Mourners) -- Israel.; Jewish mourning customs -- Israel.; Jewish women -- Israel.; Juifs yéménites -- Rites et cérémonies funéraires -- Israël.; Pleureuses -- Israël.; Deuil -- Coutumes juives -- Israël.; Juives -- Israël.; SOCIAL SCIENCE -- Death & Dying.; Jewish mourning customs; Jewish women; Weepers (Mourners); Israel